Hobbes : A Very Short Introduction - Tuck, Richard, 1949- (Oxford, New York Oxford University Press, 2002)
"Thomas Hobbes was the first great English political philosopher, and his book Leviathan was one of the first truly modern works of philosophy. He has long had the reputation of being a pessimistic atheist, who saw human nature as inevitably evil and proposed a totalitarian state to subdue human failings." "In this study, Richard Tuck dispels these myths, revealing Hobbes to have been passionately concerned with the refutation of scepticism in both sciences and ethics, and to have developed a theory of knowledge which rivalled that of Descartes in its importance for the formation of modern philosophy."--Jacket.
Include Index and Illustration
Keywords: Hobbes, Thomas, 1588-1679 -- Political science--Philosophy